Exploring Chlamydia trachomatis screening in Shenzhen: a cost-effective sample pooling strategy for pre-marital and pre-pregnancy populations - Zhang, Li; Xu, Yannan; Ye, Hailing; Xie, Yu; Tian, Lishan; Wu, Qiuhong; Ding, Yi; Zhang, Tao; Tong, Lifeng; Chen, Xiangsheng; Yuan, Jun (Frontiers in Public Health, 2025)
ObjectivesThis study evaluates the feasibility of a sample pooling strategy for Chlamydia trachomatis detection in pre-marital and pre-pregnancy screening in China, where pooled testing for CT remains limited despite its use in COVID-19 and HIV screening.MethodsFrom January to May 2024, 8,142 urine samples were collected from participants in pre-marital and pre-pregnancy health checks in Nanshan District. Positive urine samples with different Ct value ranges were selected, and negative urine samples were used as diluents to simulate mixed samples. We compared the sensitivity, specificity, and other metrics between the pooling tests and individual tests. A paired t-test was used to assess the statistical significance of the mean ΔCt values.ResultsThe 6-sample pool (1 positive:5 negative) demonstrated high sensitivity (96.7%; 95% CI: 94.1–99.3%) with a mean Ct value of 35.6 (range: 33.6–37.4). The specificity was 100% (3/3), PPV was 100% (175/175), and NPV was 33.3% (3/9). The total agreement with single testing was 96.7% (178/184; 95% CI: 94.2–99.3%). The mean ΔCt value between single and pooled tests was 2.8 (range: 2–3.2), with a statistically significant difference (p < 0.05).ConclusionThe 6-sample pooling strategy demonstrated acceptable sensitivity (96.7%) and significantly improved screening efficiency, suggesting its potential utility for large-scale pre-marital and pre-pregnancy screening programs in appropriate settings.